2019
DOI: 10.3390/microorganisms7120653
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid-Producing Yeasts: Identification and Characteristics of Environmental Isolates with a Valuable Extracellular Enzymatic Activity

Abstract: Sixteen cold-adapted reddish-pigmented yeast strains were obtained from environmental samples. According to the PCR-based detection of classical yeast markers combined with phylogenetic studies, the yeasts belong mainly to the genera Rhodotorula, Sporobolomyces and Cystobasidium, all within the subphylum Pucciniomycotina. All strains produced carotenoids within a 0.25–10.33 mg/L range under non-optimized conditions. Noteworthily, among them, representatives of the Cystobasidium genus were found; of particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…A strain of Cystofilobasidium macerans showed both cellulolytic and proteolytic activity (Chreptowicz et al, 2019). The ability to utilize various carbon sources, if combined with the production of extracellular hydrolytic enzymes, is particularly functional to the processing of agricultural wastes such as lignocellulosic biomass in the form of straw, which contains polymers composed of sugars like glucose, xylose, galactose, or cellobiose (Chreptowicz et al, 2019). The ecology of Cystobasidium lysinophilum is very particular.…”
Section: Differential Responses Of Soil Fungi To Management Systemsmentioning
confidence: 99%
“…A strain of Cystofilobasidium macerans showed both cellulolytic and proteolytic activity (Chreptowicz et al, 2019). The ability to utilize various carbon sources, if combined with the production of extracellular hydrolytic enzymes, is particularly functional to the processing of agricultural wastes such as lignocellulosic biomass in the form of straw, which contains polymers composed of sugars like glucose, xylose, galactose, or cellobiose (Chreptowicz et al, 2019). The ecology of Cystobasidium lysinophilum is very particular.…”
Section: Differential Responses Of Soil Fungi To Management Systemsmentioning
confidence: 99%
“…Previous reports demonstrated that strains from genus Cystofilobasidium were producers of pectinase, including polygalacturonase [ 65 ] and pectin lyase [ 66 ], which were important for the degradation of the polysaccharide walls of pollen grains. Cystofilobasidium macerans was also capable of secreting diverse extracellular enzymes and exhibited cellulytic and proteolytic [ 67 ] activities besides the pectinolytic activity. The significant reduction in the relative abundance of C. macerans in disordered foragers may impair their capacities in nutrient utilization.…”
Section: Discussionmentioning
confidence: 99%
“…The isolates were also investigated by conventional identification methods based on the observation of the morphology, the utilization of carbon sources, the range of growth temperature and the extracellular enzymatic activity [ 34 , 35 ]. Yeasts were deposited in a publicly available Warsaw University of Technology Yeast Collection (WUT YC) and all data can be found on (accessed on 3 November 2021) and Table S1 .…”
Section: Methodsmentioning
confidence: 99%